A food insecurity Kuznets Curve?. (May 2023) - Wesselbaum, Dennis; Smith, Michael D.; Barrett, Christopher B.; Aiyar, Anaka
Highlights: Using individual-level data representative of >96 % of the world's population, we find a Kuznets Curve relating food insecurity prevalence and inequality. Most of the world's food insecure individuals live in middle-income countries. Both macro- and micro-scale analyses confirm that intranational, interpersonal inequality in food security is greatest in the middle-income countries. Our findings emphasize the importance of identifying policies and institutions targeted to reducing food insecurity inequality, not just its prevalence. Abstract: Advances in food security proceed unevenly within and across nations. A striking pattern emerges from analysis of >560, 000 individual responses to the first globally comparable, nationally representative, repeated food insecurity survey, which is statistically representative of >96 % of the world's population. We find the relationship between the prevalence of food insecurity in a country and intranational, interpersonal inequality in food insecurity follows a strong inverse-U shape, i.e., a Kuznets Curve. The relationship is stable over time and across relevant inequality measures and estimation methods. This finding can help guide the implementation of safety nets and social protection programs to achieve the UN's Sustainable Development Goal 2 and to satisfy the human right enshrined in Article 25 of the 1948 Universal Declaration of Human Rights.